CLINICAL AND LABORATORY MANIFESTATIONS OF PURULENT-SEPTIC COMPLICATIONS OF ODONTOGENIC INFLAMMATORY DISEASES - Abdullaev, Sh.Y.; Babokhodjaev, A.S.; Boboev, K.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Diagnosis and treatment of purulent-inflammatory diseases of the maxillofacial region are currently one of the most pressing problems. This is evidenced by numerous scientific publications, conferences, symposia, congresses devoted to these issues. In the last decade, there has been a significant increase in the number of purulent-inflammatory diseases of the maxillofacial region. According to a number of authors, inflammatory diseases of the face and neck account for 10% to 30% of surgical patients who go to dental clinics, and about 50-60% of patients hospitalized in specialized dental clinics. Among them, the greatest danger to the health and life of patients is phlegmons of the maxillofacial region. In recent years, the clinical course of odontogenic purulent-inflammatory diseases has changed significantly. On the one hand, there was a significant shift in the structure of morbidity towards the prevalence of cellulitis. Progressive, including fulminant forms of purulent-inflammatory processes, spreading to several cell spaces, began to occur more frequently. The number of severe complications of purulent-inflammatory diseases of the face and neck, such as acute sepsis, toxic-infectious shock, septic meningoencephalitis, brain abscess, cerebral sinus thrombosis, arrosive bleeding, mediastinitis, septic endo- and myocarditis, which pose a threat to the life of patients, has increased. This article provides information on the clinical and laboratory manifestations of purulent-septic complications of odontogenic inflammatory diseases.